Strengthening Character Education for Students in Islamic Higher Education Institutions - Ade Lestari; Ali Imran Sinaga; Junaidi Arsyad (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Moral decline among university students has become a major challenge for Islamic higher education institutions in producing graduates with both academic competence and strong moral integrity. This study aims to analyze the implementation, impacts, and supporting and inhibiting factors of character education strengthening at STAI Al Hikmah Tebing Tinggi and STIT Batubara. Employing a qualitative multisite design, data were collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using reduction, display, conclusion drawing, and verification techniques, while validity was ensured through source and method triangulation. The findings indicate that character education is implemented through the integration of academic learning, religious habituation, student activities, and community service. These efforts contribute to improved discipline, academic responsibility, communication ethics, leadership, and social awareness among students. Institutional commitment, lecturers’ role modeling, student organizations, and supportive social environments serve as key enabling factors, whereas diverse student backgrounds, digital influences, time constraints, and limited institutional resources remain significant challenges.